Zonificación de amenazas geológicas por movimientos de masa en el barrio Sacapo de la parroquia San Pedro de Vilcabamba cantón y provincia de Loja. - Calle Torres, Janina Maribel (2010)
The zoning of geological hazards is a very useful tool for decision making, especially in the early planning stages of a project. The work presented was carried out in the Sacapo area of the Parish of San Pedro de Vilcabamba Loja Canton Province in an area of 60 hectares, it is designed to identify areas of geological hazards by mass movements. This paper is the development through the application of the method introduced by Mora and Vahrson (1992) for zoning enjoyable by mass movements, the right based on the analysis of conditioning factors (topography, geology, geomorphology, geotechnical and Vegetation Cover) and triggers (Precipitation and seismicity) and also use Geographic Information Systems (GIS), to analyze, correlate and interpret data from field while the ground sectorize homogeneous areas and rating each of these areas according to the degree of actual or potential threat. The information gathered and presented in this paper is a valuable tool that can be used in the technical zoning study area for the purpose of doing the work on mitigation and prevention as well as carry out work to detail that are designed to improve conditions current neighborhood.